The representation of malay women characters in Zurinah Hassan’s short story, ‘Anita’ / Nurhafizah Ali ... [et al.] - Ali, Nurhafizah; Muslim, Mazni; Abdul Samad, Nor Zaitolakma; Mustapha, Aida; Akmal Awang, Nurul (Universiti Teknologi MARA, Sabah, 2025)
This paper is a feminist reading of the Malaysian short story ‘Anita’ by Zurinah (1987), focusing on the representation of Malay women characters in her writing. This study analyses the characteristics of two female protagonists, ‘Anita’ and ‘I’, and the treatments they received from other characters, especially from the opposite gender. The findings suggested that the story features both reasonably strong and modest Malay women characters who are opinionated and educated. The contrast between these two women characters is mainly based on their values as either a modern or traditional woman. In the story, a woman who is single, modern, and has strong leadership skills receives unfavourable treatments from her male counterparts, while a woman who is married, leans towards traditionalism, and upholds feminine ideals face no conflicts due to her reserved and obedient nature. The narrative implies that society's prejudices toward females are underscored by the fact that women who challenge traditional gender roles face resistance, while those who conform are accepted and remain conflict-free.